2020
DOI: 10.3174/ajnr.a6411
|View full text |Cite
|
Sign up to set email alerts
|

High Intravascular Signal Arterial Transit Time Artifacts Have Negligible Effects on Cerebral Blood Flow and Cerebrovascular Reserve Capacity Measurement Using Single Postlabel Delay Arterial Spin-Labeling in Patients with Moyamoya Disease

Abstract: BACKGROUND AND PURPOSE: Arterial spin-labeling-derived CBF values may be affected by arterial transit time artefacts. Thus, our aim was to assess to what extent arterial spin-labeling-derived CBF and cerebrovascular reserve capacity values in major vascular regions are overestimated due to the arterial transit time artifacts in patients with Moyamoya disease. MATERIALS AND METHODS:Eight patients with Moyamoya disease were included before or after revascularization surgery. CBF maps were acquired using a 3D pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…No exclusions were made due to head motion, and no venous hyperintensities were found in major venous structures and cortical veins. High signal intravascular arterial transit time artifacts were generally found; however, we have previously shown that these have a negligible effect upon CBF quantification using the same method as described here (26). Structural 3D T2-weighted fluid-attenuated inversion recovery (FLAIR) and 3D contrastenhanced T1-weighted (CE-T1WI) images were acquired with spatial resolution 0.625 × 0.625 × 0.560 and 0.938 × 0.938 × 1 mm 3 for tissue segmentation and registration purposes, respectively.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 67%
“…No exclusions were made due to head motion, and no venous hyperintensities were found in major venous structures and cortical veins. High signal intravascular arterial transit time artifacts were generally found; however, we have previously shown that these have a negligible effect upon CBF quantification using the same method as described here (26). Structural 3D T2-weighted fluid-attenuated inversion recovery (FLAIR) and 3D contrastenhanced T1-weighted (CE-T1WI) images were acquired with spatial resolution 0.625 × 0.625 × 0.560 and 0.938 × 0.938 × 1 mm 3 for tissue segmentation and registration purposes, respectively.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 67%
“…The results of ASL perfusion MRI can be influenced by moyamoya vessels, which may lead to an underestimation of CBF values ( Zaharchuk et al, 2011 ). However, recent studies have suggested that the overestimation effects on the calculated CBF using single post-label delay ASL can be negligible in patients with MMD ( Fahlström et al, 2020 ). A validation study that compares it with other methods and re-evaluates it will be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Parametric maps of time-to-peak (TTP) were generated. In addition, a structural 3D T2-weighted fluid attenuated inversion recovery (FLAIR) image, 3D contrast-enhanced T1-weighted (CE-T1WI) image and 3D time-of-flight MR angiography were acquired [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%